2010
DOI: 10.1037/a0020211
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the positive role of neighborhood socioeconomic advantage in achievement: The contribution of the home, child care, and school environments.

Abstract: The goal of this study was to examine the mechanisms underlying associations between neighborhood socioeconomic advantage and children’s achievement trajectories between 54 months and 15 years old. Results of hierarchical linear growth models based on a diverse sample of 1,364 children indicate that neighborhood socioeconomic advantage was non-linearly associated with youths’ initial vocabulary and reading scores, such that the presence of educated, affluent professionals in the neighborhood had a favorable as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 84 publications
4
93
0
Order By: Relevance
“…As Flessa (2007) explained, One might link poverty to lack of employment opportunities that pay a living wage, in turn to a family's need to move frequently, in turn to inconsistent school attendance, in turn to low reading scores; or one might link poverty to economically segregated neighborhoods to low school quality to novice teachers to low reading scores. (p. 10) Similarly, based on their study of 1,364 racially diverse public school children, Dupere, Leventhal, Crosnoe, and Dion (2010) concluded that the reading score discrepancy between low-income and wealthier students could be explained largely by the institutions to which they had access since birth. For example, poor and working class families rarely have access to high-quality early childhood education programs-the kind that support children's language (and other) learning in intensive, engaging ways (Kilburn & Karoly, 2008;Temple, Reynolds, & Arteaga, 2010).…”
Section: Stereotype 4: Poor People Are Linguistically Deficientmentioning
confidence: 95%
“…As Flessa (2007) explained, One might link poverty to lack of employment opportunities that pay a living wage, in turn to a family's need to move frequently, in turn to inconsistent school attendance, in turn to low reading scores; or one might link poverty to economically segregated neighborhoods to low school quality to novice teachers to low reading scores. (p. 10) Similarly, based on their study of 1,364 racially diverse public school children, Dupere, Leventhal, Crosnoe, and Dion (2010) concluded that the reading score discrepancy between low-income and wealthier students could be explained largely by the institutions to which they had access since birth. For example, poor and working class families rarely have access to high-quality early childhood education programs-the kind that support children's language (and other) learning in intensive, engaging ways (Kilburn & Karoly, 2008;Temple, Reynolds, & Arteaga, 2010).…”
Section: Stereotype 4: Poor People Are Linguistically Deficientmentioning
confidence: 95%
“…Neighborhood and demographic characteristics influence multiple dimensions of children's development, including physical, cognitive, and social-emotional development (Dupere, Leventhal, Crosnoe, & Dion, 2010;McLoyd, 1998). Research suggests that poverty, singleparent homes, low maternal education, low maternal age, and more siblings living in the home are negatively related to child development (Brooks-Gunn, Duncan, Klebanov, & Sealand, 1993;Duncan & Brooks-Gunn, 2000).…”
Section: Neighborhood and Demographic Characteristicsmentioning
confidence: 99%
“…They found that neighborhood safety predicted children's receptive language scores, with children from unsafe neighborhoods scoring lower than children from safer neighborhoods. Dupere et al (2010) used data from a National Institute of Child Health and Human Development study to examine neighborhoods in relation to children's cognitive development. They found that children from more advantaged neighborhoods had better vocabulary and reading scores after demographic characteristics (e.g., maternal education, family income, and family structure) were controlled.…”
Section: Neighborhood and Demographic Characteristicsmentioning
confidence: 99%
“…For the latter, mothers reported the frequency with which they had observed internalizing (e.g., withdrawn, somatic complaints, anxious/depressed) and externalizing (e.g., delinquent, aggressive) behaviors or symptoms in their children on a 0–2 Likert scale. Finally, because the quality of activities, programs, and schools in part depends on the larger communities in which they are embedded, we also created a set of continuous measures tapping into neighborhood affluence (see Dupere et al, 2010) based on block group data from the 2000 Census: percent of neighborhood residents with a Bachelor’s degree, with incomes exceeding $100,000, and in professional or managerial occupations.…”
Section: Methodsmentioning
confidence: 99%